A proposal for pastoral development in the Republic of Niger - Leeuw, P.N. de; Haan, Cees de (International Livestock Centre for Africa, 1983)
Presents findings and proposals of a team which studied the pastoral zone of Niger to forumlate a development programme, describing the existing production systems and constraints related to range resources, nutrition, water points and diseases.